2021
DOI: 10.1155/2021/5581349
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Body Mass Index and Incident Diabetes Mellitus in Chinese Aged Population: A Cohort Study

Abstract: Objectives. Previous studies reported that overweight older adults had a lower mortality after cardiovascular diseases attack, indicating being thinner might not always be better. However, there is an ongoing debate about what is the optimal range of body mass index (BMI) for the aged population. We aimed to evaluate the value of BMI for the prediction of incident diabetes mellitus (DM) in the Chinese elderly population. Methods. A total number of 6,911 Chinese elderly people (4,110 men and 2,801 women, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“… 5 , they found that when BMI was approximately 22 kg/m 2 , the HR of diabetes risk of the elderly in China was approximately 1, while similar results were obtained in the study of Tang et al . 36 , the cut‐off value of BMI measured by them was approximately 22.4 kg/m 2 . These studies point out that BMI is a powerful indicator for assessing the risk of diabetes and provide potential BMI intervention thresholds for different populations.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“… 5 , they found that when BMI was approximately 22 kg/m 2 , the HR of diabetes risk of the elderly in China was approximately 1, while similar results were obtained in the study of Tang et al . 36 , the cut‐off value of BMI measured by them was approximately 22.4 kg/m 2 . These studies point out that BMI is a powerful indicator for assessing the risk of diabetes and provide potential BMI intervention thresholds for different populations.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have been carried out in the Chinese population specifically to assess the optimal BMI range or cut‐off value for predicting the risk of diabetes 33 , 34 , 35 , 36 . It is important to note that the analytical methods and conclusions used in these studies are not identical; in addition, similar to the findings of the present study, the association between BMI and diabetes does not follow the pattern of the obesity paradox.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher BMI could increase the risk of CRC [ 18 , 19 ], and BMI might have an impact on the outcomes and prognosis of CRC surgery [ 20 ]. BMI was also related to T2DM and metabolic diseases [ 21 , 22 ]. Therefore, it is necessary to analyze the exact effect of BMI on diabetic patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the ratio of hypertension and CHD was higher in the higher BMI group compared with the lower BMI group. The probable reason was that BMI was associated with metabolic and cardiovascular diseases [ 21 , 22 ]. However, there was no difference between the two groups in terms of surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%